Glutathione S tranferase PI, MI and TI genotypes and risk for colorectal cancer development in Malaysian population - Siti Nurfatimah, Mohd Shahpudin; Mohd Aminudin, Mustapha; Ahmad Aizat, Abdul Aziz; Murali Krishana, Bahavaraju Venkata; Chatar Singh, Gurjeet Kaur; Venkatesh R, Naik; Zaidi, Zakaria; Ahmad Shanwani, Mohd Sidek; Mohammad Radzi, Abu Hassan; Ankathil, Ravindran (Japan International Cultural Exchange Foundation & Japan Health Sciences University, 2011)
Background: Colorectal cancer (CRC) is a multifactorial disease with factors including dietary and lifestyle habits and genetic predisposition contributing to its etiopathogenesis. Even though the genetic predisposing factors are still unclear, genetic polymorphisms of genes encoding enzymes involved in xenobiotic metabolic pathways that activate or inactivate dietary carcinogens have been proposed as candidate genes. Three members of the Gluthathione S-Transferase (GSTs) family GSTPI, GSTT1 and GSTM1 have been analyzed in Malaysian population for polymorphic variants, and to elucidate their role in colorectal carcinogenesis. Objective: To determine the frequencies of GSTPI, GSTTI and GSTMI genotypes in 111 histopathologically confirmed CRC patients and 128 healthy controls and to evaluate the association risk of GSTPI, GSTTI and GSTMI genotypes on CRC predisposition. Material and Methods: Peripheral blood from the study subjects were collected in EDTA tubes and genomic DNA extracted using QIAGEN kit. The GSTPI IlelO5Val polymorphism was analyzed by PCR-RFLP technique using BsmAl restriction enzyme. The presence or absence of GSTM1 and GSTT1, genes were determined using a multiplex PCR protocol with albumin as the housekeeping gene. The resulting PCR fragments were separated on 2.0% agarose gel for GSTPI and 3.0% agarose gel electrophoresis for the GSTT1 and GSTM1. Results and Conclusion: On evaluating the CRC risk association with variant genotypes singly, GSTTI null genotype was associated significantly with an elevated risk (OR 1.804, 95%CI: 1.065-3.361, p=0027). When the polymorphic genotypes were analyzed in combination, the combination genotypes of GSTPI Val/Val/GSTM+/GSTTIÃ· (OR 4.000), Val/Val/GSTMI-/GSTTI- (OR 3.000), and GSTPI Ile/Ile/GSTMI+/GSTTI- (OR 2.833) showed higher associated risk for CRC susceptibility, however the risk values were not statistically significant. Further studies involving larger sample size may help to identify the more specific risk groups and to determine factors of importance in CRC development.